The social construction of "sexual knowledge": exploring the narratives of southern African youth of Indian descent in the context of HIV/AIDS - Esat, Fazila (Rhodes University, Faculty of Humanities, Department of Psychology, 2003)
This study pays attention to youth of Indian-descent within the context of sexuality and identity and their role in HIV/AIDS. By gaining an understanding of this interaction between identity and sexuality, it adds to our knowledge of the social dynamics that contribute to the prevalence or lack of prevalence of HIV/AIDS within population groups. This study uses a social constructionist discourse analytic framework and aims to explore the construction of sexual knowledge by Southern African youth of Indian-descent. The findings indicate that the construction of sex is primarily one of risk and ambiguity. Additionally, the construction of sexual knowledge highlights the significance of gender differentials and the importance of agency and responsibility for sexual education. These constructions reinforce traditional educational roles that contribute to the construction of sex as risky and ambiguous. In addition, a social identity of Indian-ness and othering is used as a strategy to give meaning to the lack of parental responsibility with regard to sexual education. The use of social identity is seen as highlighting the importance of acknowledging the sexual values within which youth are embedded. This study concludes with possible ways to shift these constructions. For example, one of the conclusions suggests the implementation of an alternative school-based sexual education that acknowledges the sexual values in which youth are embedded. Furthermore, this acknowledgement of sexual values should take place within a holistic sex education programme that is positive about sexuality. Additionally, a reframing of youth as capable and active decision-makers in their sexual education is necessitated in order to see youth as a potential resource in HIV/AIDS prevention.
Keywords: East Indians -- South Africa -- Attitudes; Youth -- South Africa -- Attitudes; East Indians -- South Africa -- Sexual behavior; Youth -- South Africa -- Sexual behavior; AIDS (Disease) -- Social aspects -- South Africa; HIV infections -- Social aspects -- South Africa